Association between neutrophil to lymphocyte ratio and depressive symptoms among Chinese adults: A population study from the TCLSIH cohort study. (May 2019) - Meng, Ge; Wang, Liu; Wang, Xiaona; Chi, Vu Thi Quynh; Zhang, Qing; Liu, Li; Yao, Zhanxin; Wu, Hongmei; Bao, Xue; Gu, Yeqing; Zhang, Shunming; Sun, Shaomei; et al.
Highlights: NLR is positively related to depressive symptoms in women, but not in men. This is a general population study on the association of NLR and depressive symptoms. Our results indicate a sex-specific association between inﬂammation and depression. Abstract: Background: The prevalence of depression in the general population has risen sharply over the past few decades and has become a major health problem throughout the world. Increasing evidence suggests that inflammation plays an important role in the pathogenesis of depression. To better understand the role of inflammation in the pathogenesis of depression we can use the neutrophil-to-lymphocyte ratio (NLR) because it is a simple and effective marker of inflammation and immunity. Methods: This cross-sectional study was conducted among adults from the healthy general population in Tianjin, China. NLR was measured according to the complete blood count. Depressive symptoms were assessed using the Zung Self-Rating Depression Scale (SDS), and a cutoff score of 45 was used to indicate the presence of depressive symptoms in the study participants. The relationship between NLR and the prevalence of depressive symptoms was evaluated separately for men and women using the multiple logistic regression analysis. Results: In the present study, the overall prevalence of depressive symptoms was 17.0% among all participants. In women, the multivariable-adjusted OR of having depressive symptoms was 1.28 (95% CI 1.10, 1.49; p for trend <0.01) for the fifth compared with the first quintile of NLR, and was 1.22 (95% CI 1.07, 1.39; p < 0.01) per unit increase of NLR. However, no significant association was found between NLR and depressive symptoms in men. Conclusion: This study suggests that increased NLR levels are independently related to depressive symptoms in women, but not in men. Further research is required to investigate this relationship with longitudinal data to establish the temporal ordering between these variables.